Semelparous whitefish Coregonus lavaretus: do they exist? - Jan Henning L'Abee-Lund; Einar Kleven; Dag Matzow; Odd Terje Sandlund (Fauna Norvegica, 1988)
The life history of the whitefish Coregonus lavaretus population in the eutrophic Lake Temse, Southern Norway, was studied in 1985 and 1986. Growth was intermediate compared to other populations, whitefish attained 13 and 21 cm first and second winter, respectively. The population was dominated (91%) by the age groups 0, 1 and 2. Oldest aged male and female whitefish were 6 and 4 years, respectively. Fishing pressure and emigration could not explain the observed age structure and age at sexual maturity, but evolution towards semelparity and optimal age at sexual maturity could. Restricted spawning areas are suggested as being the principal factor in the development of semelparity in the population of whitefish studied.